GENDER DIFFERENCES IN CO-MORBID DISORDERS WITH ATTENTION-DEFICIT HYPERACTIVITY DISORDER (ADHD) - Herbani, Paria; Behdan, Fatemeh (Journal of Pakistan Psychiatric Society, 2007)
Objective: To assess the impact of gender on co-morbid disorders with Attention-Deficit Hyperactivity Disorder (ADHD).Design: Cross sectional study.Place and duration of study: We selected children and adolescents with ADHD referred to the Sheikh Hospital clinic (a subspecialty hospital for children in Mashhad, Iran) between November 2002 and March 2004.Subjects and Methods:Two-stage ascertainment procedure was used to select the subjects. The first stage was the patient’s referral to a psychiatric clinic resulting in a clinical diagnosis of ADHD by a child psychiatrist. A second stage confirmed the diagnosis of ADHD made on face-to-face structured interviews with the mother. Only patients who received a diagnosis of ADHD at all two stages were included in the final analysis. The clinical interview and the Schedule for Affective Disorders and Schizophrenia for School – Age Children Present and Lifetime version (K – SADS – PL) were used for making diagnosis according to DSM-IV.Results: There is no meaningful statistically significant differences in the sex of probands. the proportion of male was 48.3 %( n=71) and female 51.7 %( n=76). The majority of probands were between 7-12 years old (68%). Although mood disorders (depressive disorders and bipolar), anxiety disorders and enuresis were more common in males but there were no significant differences between them. OCD and Learning disorders were more prevalent in girls but the difference was not statistically significant.Conclusion: Our results suggest that boys and girls do not differ in the co-morbid disorders with ADHD. Although this is consistent with prior work suggesting more similarities than differences in the nature of psychiatric co-morbidity in ADHD boys and girls, we cannot make strong conclusions, thus replication studies are needed.Key words: ADHD, Gender Differences, Co-morbid Disorders.